Effect of Denosumab on Bone Mineral Density and Markers of Bone Turnover among Postmenopausal Women with Osteoporosis - A. Sánchez; L. R. Brun; H. Salerni; P. R. Costanzo; D. González; A. Bagur; B. Oliveri; M. B. Zanchetta; V. Farías; L. Maffei; V. Premrou; J. L. Mansur; et al. (Journal of Osteoporosis)
The aim of this study was to evaluate the effect of denosumab (Dmab) on bone mineral density (BMD) and bone turnover markers after 1 year of treatment. Additionally, the effect of Dmab in bisphosphonate-naïve patients (BP-naïve) compared to patients previously treated with bisphosphonates (BP-prior) was analyzed. This retrospective study included 425 postmenopausal women treated with Dmab for 1 year in clinical practice conditions in specialized centers from Argentina. Participants were also divided according to previous bisphosphonate treatment into BP-naïve and BP-prior. A control group of patients treated with BP not switched to Dmab matched by sex, age, and body mass index was used. Data are expressed as mean ± SEM. After 1 year of treatment with Dmab the bone formation markers total alkaline phosphatase and osteocalcin were significantly decreased (23.36% and 43.97%, resp.), as was the bone resorption marker s-CTX (69.61%). Significant increases in BMD were observed at the lumbar spine, femoral neck, and total hip without differences between BP-naïve and BP-prior. A better BMD response was found in BP-prior group compared with BP treated patients not switched to Dmab. Conclusion. Dmab treatment increased BMD and decreased bone turnover markers in the whole group, with similar response in BP-naïve and BP-prior patients. A better BMD response in BP-prior patients versus BP treated patients not switched to Dmab was observed.